Fast and Efficient Method for Imination of N-Aminorhodanine Using Inorganic Solid Support under Microwave Irradiation and Classical Heating - Masoumeh Tabatabaee; Majid M. Heravi; Mahboubeh Sharif; Fatemeh Esfandiyari (E-Journal of Chemistry)
Reaction of N-aminorhodanine with various aldehydes under classical heating (in various solvents, using hydrochloric acid or acetic acid as catalyst) or by using Al2O3 under microwave irradiation in solventless system led to the corresponding imines (2 or 3). All the compounds have been characterized by elemental analyses, NMR and IR spectroscopy. Results indicate that treatment of N-aminorhodanine with aldehydes in acetonitrile as solvent or under solventless system led to the corresponding imines (2a-2e), while reactions were performed in solvent such as methanol 3a-3e was formed as products of ring cleavage and imination.